Effects on the photon beam from an electromagnetic array used for patient localization and tumor tracking. (6th May 2013) - Zou, Wei; Betancourt, Ricardo; Yin, Lingshu; Metz, James; Avery, Stephen; Kassaee, Alireza
Abstract : One of the main components in a Calypso 4D localization and tracking system is an electromagnetic array placed above patients that is used for target monitoring during radiation treatment. The beam attenuation and beam spoiling properties of the Calypso electromagnetic array at various beam angles were investigated. Measurements were performed on a Varian Clinac iX linear accelerator with 6 MV and 15 MV photon beams. The narrow beam attenuation properties were measured under a field size of 1 c m × 1 c m, with a photon diode placed in a cylindrical graphite buildup cap. The broad beam attenuation properties were measured under a field size of 10 c m × 10 c m, with a 0.6 cc cylindrical Farmer chamber placed in a polystyrene buildup cap. Beam spoiling properties of the array were studied by measuring depth‐dose change from the array under a field size of 10 c m × 10 c m cm in a water‐equivalent plastic phantom with an embedded Markus parallel plate chamber. Change in depth doses were measured with the array placed at distances of 2, 5, and 10 cm from the phantom surface. Narrow beam attenuation and broad beam attenuation from the array were found to be less than 2%–3% for both 6 MV and 15 MV beams at angles less than 40°, and were more pronounced at more oblique angles. Spoiling effects are appreciable at beam buildup region, but are insignificant at depths beyond d max . Dose measurements in a QA phantom using patient IMRT and VMAT treatment plans were shown to have less than 2.5% dose difference with the Calypso array. The results indicate that the dose difference due to the placement of Calypso array is clinically insignificant. PACS number: 87.56.‐v